Strategi Pengelolaan Sarana Prasarana Pendidikan untuk Menciptakan Lingkungan Belajar yang Kondusif: Penelitian - Slamet Riyadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to determine the strategy for managing educational facilities and infrastructure to create a conducive learning environment. This research approach collects data through a literature study, which involves reading literature from various sources including books, reports, articles, and journals using qualitative and deductive approaches. The results of this study are that the management of educational facilities and infrastructure is a key factor in creating a conducive learning environment. This process includes planning, procurement, inventory, arrangement, use, maintenance, and disposal of facilities so that they can function optimally in supporting learning. However, its implementation often faces various challenges such as budget constraints, weak planning, lack of competent human resources, technological developments, and regulatory changes. To overcome these challenges, strategies that can be taken include optimizing the use of existing facilities, using information technology, increasing teacher creativity, collaborating with external parties, utilizing public facilities, and developing educator competencies on an ongoing basis. With this approach, schools can manage facilities and infrastructure effectively while creating a conducive learning environment.